A novel enzyme with spermine oxidase properties in bovine liver mitochondria: identification and kinetic characterization - Bonaiuto, Emanuela; Grancara, Silvia; Martinis, Pamela; Stringaro, Annarita; Colone, Marisa; Agostinelli, Enzo; Macone, Alberto; Stevanato, Roberto; Vianello, Fabio; Toninello, Antonio; Di Paolo, Maria Luisa (Free radical biology & medicine, 2015)
The uptake of spermine into mammalian mitochondria indicated the need to identify its catabolic pathway in these organelles. Bovine liver mitochondria were therefore purified and their capacity for natural polyamine uptake was verified. A kinetic approach was then used to determine the presence of an MDL 72527-sensitive enzyme with spermine oxidase activity in the matrix of bovine liver mitochondria. Western blot analysis of mitochondrial fractions and immunogold electron microscopy observations of purified mitochondria unequivocally confirmed the presence of a protein recognized by anti-spermine oxidase antibodies in the mitochondrial matrix. Preliminary kinetic characterization showed that spermine is the preferred substrate of this enzyme; lower activity was detected with spermidine and acetylated polyamines. Catalytic efficiency comparable to that of spermine was also found for 1-aminododecane. The considerable effect of ionic strength on the Vmax/KM ratio suggested the presence of more than one negatively charged zone inside the active site cavity of this mitochondrial enzyme, which is probably involved in the docking of positively charged substrates. These findings indicate that the bovine liver mitochondrial matrix contains an enzyme belonging to the spermine oxidase class. Because H2O2 is generated by spermine oxidase activity, the possible involvement of the latter as an important signaling transducer under both physiological and pathological conditions should be considered.
Keywords: Liver; Cattle; jaterní mitochondrie; Animals; Mitochondria, Liver; skot; Hydrogen Peroxide; Oxidoreductases Acting on CH-NH Group Donors; Polyamine Oxidase; Kinetics; Spermidine; játra; Mitochondria; polyaminoxidasa; Substrate Specificity; Polyamines; statická elektřina; Spermine; peroxid vodíku; Osmolar Concentration; Immunogold; Putrescine; oxidace-redukce; Polyamine oxidases; putrescin; osmolární koncentrace; katalytická doména; Oxidation-Reduction; Spermine oxidase; Static Electricity; spermin; zvířata; substrátová specifita; oxidoreduktasy působící na CH-NH vazby; spermidin; kinetika; Catalytic Domain